Ethylene-vinyl alcohol copolymer resin composition, film and multilayer structure

By integrating a metal compound with specific X-ray diffraction properties into ethylene-vinyl alcohol-based copolymer films, the films achieve superior gas barrier properties, particularly under high humidity conditions, effectively addressing the limitations of existing technologies.

JP7669927B2Active Publication Date: 2025-04-30MITSUBISHI CHEM CORP
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2021539265
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-11-29
Filing Date
2020-08-07
Publication Date
2025-04-30
Estimated Expiration
2040-08-07

AI Technical Summary

Technical Problem

Ethylene-vinyl alcohol-based copolymer films exhibit reduced gas barrier properties, particularly oxygen barrier properties, under high humidity due to the active hydroxyl groups in the polymer molecules.

Method used

Incorporating a metal compound with an X-ray diffraction peak between 2θ and 15° when measured using wide-angle X-ray diffraction with CuKα rays into the ethylene-vinyl alcohol-based copolymer resin composition, which enhances the gas barrier properties under high humidity.

Benefits of technology

The resulting film demonstrates excellent gas barrier properties, especially oxygen barrier properties, under high humidity conditions, with an oxygen permeability of 15cc · 20μm/m² ·day ·atm or less at 20°C and 90%RH.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007669927000001
    Figure 0007669927000001
Patent Text Reader

Abstract

Provided is an ethylene-vinyl alcohol copolymer resin composition having excellent gas barrier performance under high humidity, and particularly having excellent oxygen barrier performance under high humidity. This ethylene-vinyl alcohol copolymer composition contains an ethylene-vinyl alcohol copolymer and a metal compound, and in a wide angle X-ray diffraction analysis using CuKα rays, demonstrates a peak at 2θ = 2° to 15°.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an ethylene-vinyl alcohol copolymer resin composition, and more particularly to an ethylene-vinyl alcohol copolymer resin composition from which a film having high gas barrier properties can be obtained under high humidity conditions. [Background technology]

[0002] Ethylene-vinyl alcohol copolymers have excellent transparency, gas barrier properties such as oxygen and other gases, aroma retention, solvent resistance, oil resistance, mechanical strength, etc., and are formed into films, sheets, bottles, etc. and are widely used as various packaging materials such as food packaging materials, pharmaceutical packaging materials, industrial chemical packaging materials, and agricultural chemical packaging materials.

[0003] However, since ethylene-vinyl alcohol copolymers have relatively active hydroxyl groups in their molecules, they are highly susceptible to the effects of humidity, and their gas barrier properties decrease significantly in high humidity environments.

[0004] Patent Document 1 discloses an ethylene-vinyl alcohol copolymer film in which an inorganic compound is uniformly dispersed in an ethylene-vinyl alcohol copolymer, as an ethylene-vinyl alcohol copolymer film having improved gas barrier properties.

[0005] Furthermore, Patent Document 2 discloses an ultraviolet ray shielding film having excellent transparency, which is obtained by satisfactorily dispersing ultrafine zinc oxide particles in an ethylene-vinyl alcohol copolymer. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] International Publication No. 2016 / 088862 [Patent Document 2] JP 2004-91521 A DISCLOSURE OF THEINVENTION [Problem to be solved by the invention]

[0007] However, although the film disclosed in Patent Document 1 improves the gas barrier property by dispersing an inorganic compound in an ethylene-vinyl alcohol copolymer, the gas barrier property under high humidity conditions is insufficient, and further improvement is required. In addition, although Patent Document 2 provides a film containing zinc oxide ultrafine particles in an ethylene-vinyl alcohol copolymer, the gas barrier property under high humidity conditions is insufficient because the film does not address the issue of improving the gas barrier property under high humidity conditions, and further improvement is required.

[0008] In view of the above, the present invention provides an ethylene-vinyl alcohol copolymer resin composition having excellent gas barrier properties under high humidity, particularly excellent oxygen barrier properties under high humidity. [Means for solving the problem]

[0009] However, the present inventors have found that an ethylene-vinyl alcohol copolymer resin composition that contains a metal compound and has an X-ray diffraction peak at 2θ=2 to 15° when measured by wide-angle X-ray diffraction using CuKα radiation has excellent gas barrier properties under high humidity conditions.

[0010] That is, a first gist of the present invention is an ethylene-vinyl alcohol-based copolymer resin composition that contains an ethylene-vinyl alcohol-based copolymer and a metal compound and has an X-ray diffraction peak at 2θ=2 to 15° when measured by wide-angle X-ray diffraction using CuKα radiation. A second aspect of the present invention is a film containing the ethylene-vinyl alcohol copolymer resin composition according to the first aspect, and a third aspect of the present invention is a multilayer structure having at least one layer made of the film according to the second aspect. Effect of the Invention

[0011] The ethylene-vinyl alcohol copolymer resin composition of the present invention contains an ethylene-vinyl alcohol copolymer and a metal compound, and has an X-ray diffraction peak at 2θ=2 to 15° when measured by wide-angle X-ray diffraction using CuKα radiation. When ethylene-vinyl alcohol copolymer molecules or water molecules are present around the compound having this diffraction peak, they interact with the ethylene-vinyl alcohol copolymer at the molecular level, resulting in a film made of this ethylene-vinyl alcohol copolymer resin composition having excellent gas barrier properties, particularly oxygen barrier properties, under high humidity conditions.

[0012] When the content of the metal compound in terms of metal is 0.01 to 10 parts by weight per 100 parts by weight of the ethylene-vinyl alcohol copolymer, the resulting film can have excellent gas barrier properties, particularly oxygen barrier properties, under high humidity conditions.

[0013] When the metal species contained in the metal compound is at least one selected from Zn, Co and Ni, the resulting film can have excellent gas barrier properties, particularly oxygen barrier properties, under high humidity conditions.

[0014] A film containing the ethylene-vinyl alcohol copolymer resin composition of the present invention can have excellent gas barrier properties, particularly oxygen barrier properties, under high humidity conditions.

[0015] The oxygen permeability of the above film at 20℃ and 90% RH is 15cc·20μm / m 2 When the humidity is 100% or less, the gas barrier property, particularly the oxygen barrier property, can be improved under high humidity conditions.

[0016] A multilayer structure having at least one layer made of the above film can have excellent gas barrier properties, particularly oxygen barrier properties, under high humidity conditions. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0017] Hereinafter, embodiments for carrying out the present invention will be specifically described, but the present invention is not limited thereto. In the present invention, the "ethylene-vinyl alcohol copolymer" may be referred to as "EVOH".

[0018] <EVOH resin composition> The EVOH resin composition of the present invention contains EVOH and a metal compound.

[0019] Further, the EVOH resin composition of the present invention has a main peak of X-ray diffraction at 2θ = 2 to 15° when measured by wide-angle X-ray diffraction using CuKα rays, from the viewpoint of excellent gas barrier properties, particularly oxygen barrier properties, under high humidity. Furthermore, it preferably has a main peak at 2θ = 2 to 9°, and particularly preferably has a main peak at 2θ = 3 to 8°.

[0020] In the present invention, it is presumed that when a compound having a main peak of X-ray diffraction at 2θ = 2 to 15° measured by wide-angle X-ray diffraction using the above CuKα rays interacts with EVOH, the polarity of EVOH increases, resulting in an excellent oxygen barrier property under high humidity.

[0021] Also, the compound having a main peak of X-ray diffraction at 2θ = 2 to 15° is preferably a peak derived from a metal compound.

[0022] The wide-angle X-ray diffraction is measured under the following conditions. [Measurement conditions] · Equipment used: D8 DISCOVER (manufactured by Bruker Japan) · Detector: 2D detector VANTEC-500 (manufactured by Bruker Japan) · Voltage: 50 kV · Current: 100 mA · Camera length: 100 mm · Measurement method: Reflection method · Integration time: 30 minutes or 60 minutes Wavelength: CuKα radiation (Kα1 and Kα2 are not separated) Detector position: 2θ=10° ·X-ray incident angle: θ=0.3° ·Conditions for one-dimensionalization in the 2θ direction: 2θ=0~35°, azimuth angle (chi)=-95~-85° ·Azimuth direction one-dimensional: Azimuth angle (chi)=-180~0° When the diffraction peak is one-dimensionalized in the azimuth direction, the diffraction peak is one-dimensionalized in the range of 1.0° so that the peak with the strongest diffraction intensity is included in the range of 2θ=2 to 15°. In this case, if a peak is observed in the range of azimuth angles -180 to 0°, it is determined that the diffraction peak is observed in the range of 2θ=2 to 15°. For example, if a diffraction peak is observed at 2θ=6.8°, when the diffraction peak is one-dimensionalized in the azimuth direction in the range of 2θ=6.0 to 7.0°, if a peak is observed in the range of azimuth angles = -180 to 0°, it may be determined that the diffraction peak is observed in the range of 2θ=2 to 15°.

[0023] As a sample to be used for the wide-angle X-ray diffraction, the EVOH resin composition in the form of a film described below may be used as it is. When the film of the EVOH resin composition is laminated with another substrate, if the EVOH resin composition layer can be peeled off, the EVOH resin composition layer is peeled off and measurement is performed, and if the EVOH resin composition layer cannot be peeled off, the measurement may be performed while the film is laminated with the other substrate. At the time of measurement, the thickness of the peeled EVOH resin composition layer (film) is preferably 30 μm or more, and if the film is not thick enough, a film may be laminated.

[0024] The EVOH contained in the EVOH resin composition of the present invention will be described below.

[0025] [EVOH] The EVOH is a resin obtained by saponifying an ethylene-vinyl ester copolymer, which is a copolymer of ethylene and a vinyl ester monomer, and is a water-insoluble thermoplastic resin. Vinyl acetate is generally used as the vinyl ester monomer from an economical point of view.

[0026] The polymerization of ethylene and vinyl ester monomers can be carried out by any known polymerization method, such as solution polymerization, suspension polymerization, or emulsion polymerization, and generally, solution polymerization using methanol as a solvent is used. The saponification of the obtained ethylene-vinyl ester copolymer can also be carried out by a known method.

[0027] The EVOH produced in this manner is mainly composed of structural units derived from ethylene and vinyl alcohol structural units, and usually contains a small amount of vinyl ester structural units that remain unsaponified.

[0028] As the vinyl ester monomer, vinyl acetate is typically used because of its good market availability and efficiency in treating impurities during production. Other vinyl ester monomers include, for example, aliphatic vinyl esters such as vinyl formate, vinyl propionate, vinyl valerate, vinyl butyrate, vinyl isobutyrate, vinyl pivalate, vinyl caprate, vinyl laurate, vinyl stearate, and vinyl versatate, and aromatic vinyl esters such as vinyl benzoate. Usually, aliphatic vinyl esters having 3 to 20 carbon atoms, preferably 4 to 10 carbon atoms, and particularly preferably 4 to 7 carbon atoms can be used. These can be used alone or in combination of two or more kinds.

[0029] The content of the ethylene structural unit in the EVOH can be controlled by the ethylene pressure when the vinyl ester monomer and ethylene are copolymerized, and is usually 20 to 60 mol%, preferably 25 to 50 mol%, and particularly preferably 25 to 35 mol%. If the content is too low, the gas barrier property and melt moldability under high humidity tend to decrease, and conversely, if it is too high, the gas barrier property tends to decrease. The content of the ethylene structural unit can be measured based on ISO14663.

[0030] The degree of saponification of the vinyl ester component in EVOH can be controlled by the amount, temperature, time, etc. of the saponification catalyst (usually an alkaline catalyst such as sodium hydroxide is used) used when saponifying an ethylene-vinyl ester copolymer, and is usually 90 to 100 mol%, preferably 95 to 100 mol%, and particularly preferably 99 to 100 mol%. If the degree of saponification is too low, the gas barrier properties, heat stability, moisture resistance, etc. tend to decrease. The degree of saponification of the EVOH can be measured based on JIS K6726 (wherein the EVOH is used as a solution uniformly dissolved in a water / methanol solvent).

[0031] The melt flow rate (MFR) of the EVOH (210°C, load 2160 g) is usually 0.5 to 100 g / 10 min, preferably 1 to 50 g / 10 min, and particularly preferably 3 to 35 g / 10 min. If the MFR is too high, the film formability tends to be unstable, whereas if the MFR is too low, the viscosity tends to be too high, making melt extrusion difficult. The MFR is an index of the degree of polymerization of EVOH, and can be adjusted by the amount of polymerization initiator and the amount of solvent used when copolymerizing ethylene with a vinyl ester monomer.

[0032] In addition, EVOH may further contain structural units derived from the comonomers shown below within a range that does not impair the effects of the present invention (for example, 10 mol % or less of EVOH). Examples of the comonomers include olefins such as propylene, 1-butene, and isobutene; hydroxyl-containing α-olefins such as 3-buten-1-ol, 3-butene-1,2-diol, 4-penten-1-ol, and 5-hexene-1,2-diol, as well as their esterified and acylated derivatives; hydroxyalkylvinylidenes such as 2-methylenepropane-1,3-diol and 3-methylenepentane-1,5-diol; 1,3-diacetoxy-2-methylenepropane, 1,3-dipropionyloxy-2-methylenepropane, and 1,3-dibutyryloxy. -Hydroxyalkylvinylidene diacetates such as 2-methylenepropane; unsaturated acids such as acrylic acid, methacrylic acid, crotonic acid, (anhydrous) phthalic acid, (anhydrous) maleic acid, (anhydrous) itaconic acid, or their salts or mono- or dialkyl esters in which the alkyl group has 1 to 18 carbon atoms; acrylamide, N-alkylacrylamide in which the alkyl group has 1 to 18 carbon atoms, N,N-dimethylacrylamide, 2-acrylamidopropanesulfonic acid or its salts, acrylamidopropyldimethylamine or its acid salts or its quaternary salts, etc. acrylamides such as methacrylamide, N-alkyl methacrylamides in which the alkyl group has 1 to 18 carbon atoms, N,N-dimethyl methacrylamide, 2-methacrylamidopropanesulfonic acid or its salt, methacrylamidepropyldimethylamine or its acid salt or its quaternary salt, and other methacrylamides; N-vinylpyrrolidone, N-vinylformamide, N-vinylacetamide, and other N-vinylamides; vinyl cyanides such as acrylonitrile and methacrylonitrile; alkyl vinyl ethers in which the alkyl group has 1 to 18 carbon atoms, hydrochloride, etc. vinyl ethers such as alkoxyalkyl vinyl ether and alkoxyalkyl vinyl ether; halogenated vinyl compounds such as vinyl chloride, vinylidene chloride, vinyl fluoride, vinylidene fluoride and vinyl bromide; vinyl silanes such as trimethoxyvinylsilane; halogenated allyl compounds such as allyl acetate and allyl chloride; allyl alcohols such as allyl alcohol and dimethoxyallyl alcohol; and comonomers such as trimethyl-(3-acrylamido-3-dimethylpropyl)-ammonium chloride and acrylamido-2-methylpropanesulfonic acid.These can be used alone or in combination of two or more.

[0033] In particular, EVOH having a primary hydroxyl group in the side chain is preferred because it has good secondary formability while maintaining gas barrier properties. Among these, EVOH copolymerized with hydroxyl group-containing α-olefins is preferred, and EVOH having a 1,2-diol structure in the side chain is particularly preferred. In particular, in the case of EVOH having a primary hydroxyl group in the side chain, the content of structural units derived from a monomer having the primary hydroxyl group is usually 0.1 to 20 mol %, preferably 0.5 to 15 mol %, and particularly preferably 1 to 10 mol % of the EVOH.

[0034] The EVOH used in the present invention may be "post-modified" such as urethanized, acetalized, cyanoethylated, oxyalkylenated, or acylated.

[0035] Furthermore, the EVOH used in the present invention may be a mixture with other different EVOHs, and such other EVOHs may include those having a different degree of saponification, a different degree of polymerization, or different copolymerization components.

[0036] The EVOH is preferably the main component of the EVOH resin composition, and the content of the EVOH in the entire EVOH resin composition is usually 80% by weight or more, preferably 90% by weight or more, and particularly preferably 95% by weight or more. The upper limit is usually 99.99% by weight.

[0037] As described above, the EVOH resin composition of the present invention contains the above-mentioned EVOH and a metal compound, and has an X-ray diffraction peak at 2θ=2 to 15° when measured by wide-angle X-ray diffraction using CuKα radiation.

[0038] [Metal compound] The metal compound preferably has a structure in which a specific structural unit is layered with a specific interplanar spacing, and is particularly preferably a metal-containing layered compound.The metal compound preferably does not have an oxo ligand.If the metal compound has an oxo ligand, the interaction with EVOH is weak, and sufficient gas barrier properties tend not to be obtained.

[0039] Examples of the metal species contained in the metal compound include Na, K, Ca, Ti, Cr, Mn, Fe, Co, Ni, Cu, and Zn. These metal species may be contained alone or in combination. Among them, Ni, Co, and Zn are particularly preferred, and Zn is particularly preferred, in terms of excellent oxygen barrier properties under high humidity conditions.

[0040] The metal compounds used in the present invention exclude common clay minerals such as gibnite, kaolinite, illite / mica, smectite, vermiculite, chlorite, iron compounds, quartz, amorphous minerals, and carbonate minerals.

[0041] The interlayer distance (distance between layers) of the metal-containing layered compound is preferably 0.01 to 50 nm, more preferably 0.1 to 30 nm, from the viewpoint of interaction with EVOH molecules and water molecules. The interlayer distance of the metal-containing layered compound can be calculated from the Bragg formula based on the diffraction position of the strongest peak in the range of 2θ=2 to 15° when analyzed by X-ray diffraction method.

[0042] The molecular weight of the layered structural unit peeled off from the metal-containing layered compound is preferably 100 to 10,000, particularly preferably 200 to 2,000, in view of the ability to interact with EVOH at the molecular level.

[0043] In addition, the layered structural unit is preferably hydrophilic in terms of interaction with EVOH molecules. Furthermore, it is preferable that the layered structural unit does not decompose even when left to stand in an environment of 20° C. and 90% RH for 1,000 hours.

[0044] The content of the metal compound in the EVOH resin composition in terms of metal is usually 0.01 to 10 parts by weight, preferably 0.05 to 8 parts by weight, particularly preferably 0.1 to 5 parts by weight, and particularly preferably 0.2 to 3 parts by weight, relative to 100 parts by weight of EVOH. If the content of the metal compound is too low, the oxygen barrier property under high humidity conditions tends to decrease, whereas if the content of the metal compound is too high, whitening and reduced transparency tend to occur when the composition is made into a film or the like. When the EVOH resin composition contains a plurality of metal compounds each having a different metal species, the total amount of all the metal compounds contained in the EVOH resin composition is defined as the content. The content of the metal compounds can be determined by the standard addition method using ICP-MS.

[0045] The EVOH resin composition of the present invention can be prepared, for example, by (I) a method of reacting a metal-containing compound with a base in a solution in which EVOH has been dissolved, (II) a method of heating a metal-containing compound in a solution in which EVOH has been dissolved to cause a reaction, or (III) a method of mixing EVOH with a metal compound that has previously been reacted with a metal-containing compound and a base.

[0046] Examples of the metal species contained in the metal-containing compound include the metal species described above for the metal compound, and among these, Ni, Co, and Zn are preferred, with Zn being more preferred.

[0047] Examples of the metal-containing compound include organic acid metal salts, inorganic metal salts, etc. Among these, organic acid metal salts are preferred from the viewpoint of reactivity.

[0048] Examples of organic acids constituting the organic acid metal salt include monovalent carboxylic acids such as acetic acid and hydroxyalkyl carboxylic acids having an alkyl group with 2 to 20 carbon atoms, divalent carboxylic acids such as succinic acid, oxalic acid, and tartaric acid, and trivalent or higher carboxylic acids such as citric acid and ethylenediaminetetraacetic acid. These may be used alone or in combination of two or more. The organic acid metal salt may be a hydrate or an anhydride. As the organic acid metal salt, a monovalent carboxylate metal salt is preferred from the viewpoint of excellent oxygen barrier properties under high humidity conditions, and particularly preferred are metal acetates and metal salts of hydroxyalkylcarboxylates having an alkyl group with 2 to 20 carbon atoms, and particularly preferred are zinc acetate and zinc hydroxyalkylcarboxylates having an alkyl group with 2 to 20 carbon atoms, and further preferably zinc acetate, zinc hydroxyalkylcarboxylates having an alkyl group with 2 to 8 carbon atoms, or hydrates thereof.

[0049] Examples of the inorganic metal salt include metal fluorides, chlorides, bromides, iodides, and oxoacids. These may be used alone or in combination of two or more. The inorganic metal salt may be a hydrate or an anhydride. Of these, the inorganic metal salt is preferably a metal chloride or an oxoacid, because of its excellent oxygen barrier properties under high humidity conditions, and particularly preferably zinc chloride, zinc nitrate or a hydrate thereof.

[0050] Each method for preparing the EVOH resin composition will be described in detail below.

[0051] [Method (I)] The above method (I) is a method in which a metal-containing compound is reacted with a base in a solution in which EVOH is dissolved.

[0052] Examples of the base used in the above method (I) include hydroxides of alkali metals or alkaline earth metals. Among them, hydroxides of alkali metals are preferred, and sodium hydroxide is particularly preferred, because they have excellent reactivity with metal-containing compounds.

[0053] In the reaction between the metal-containing compound and the base, the metal-containing compound and the base may be usually mixed in a solution in which EVOH is dissolved, and then the reaction may be carried out. The method of mixing the metal-containing compound and the base is not particularly limited, and examples thereof include a method of mixing a solution in which a metal-containing compound is dissolved with a solution in which a base is dissolved, and a method of mixing a slurry liquid in which a metal-containing compound is dispersed with a solution in which a base is dissolved. In addition, EVOH may be dissolved in at least one of a solution in which a metal-containing compound is dissolved or a slurry liquid in which a metal-containing compound is dispersed and a solution in which a base is dissolved. Among the above methods, a method of mixing a solution in which a metal-containing compound is dissolved with a solution in which a base is dissolved is preferred from the viewpoint of reaction efficiency. Furthermore, when an organic acid metal salt is used as the metal-containing compound, a method of adding a solution in which an organic acid metal salt is dissolved to a solution in which a base is dissolved and mixing them is preferred, and when an inorganic metal salt is used, a method of adding a solution in which a base is dissolved to a solution in which an inorganic metal salt is dissolved and mixing them is preferred.

[0054] The solvent for dissolving or dispersing the EVOH, the metal-containing compound, and the base is not particularly limited, and examples thereof include water, methanol, ethanol, 1-propanol, 2-propanol, 1-butanol, 2-butanol, and other lower alcohols having 1 to 5 carbon atoms. These may be used alone or in combination of two or more. Among these, water and alcohols are preferred, and a mixed solvent of water and 1-propanol is particularly preferred.

[0055] The concentration of the metal-containing compound in the solution in which the metal-containing compound is dissolved or in the slurry in which the metal-containing compound is dispersed is usually 0.01 to 3 mol / L, and preferably 0.05 to 2 mol / L. The concentration of the base in the solution in which the base is dissolved is usually 0.01 to 100 mol / L, preferably 0.05 to 30 mol / L, and particularly preferably 0.1 to 10 mol / L. If the concentrations of the metal-containing compound and the base are lower than the above ranges, the reaction tends not to proceed sufficiently, whereas if the concentrations of the metal-containing compound and the base are higher than the above ranges, side reactions tend to occur.

[0056] The molar ratio of the metal-containing compound to the base (metal-containing compound:base) is usually 0.5:2 to 2:0.5, preferably 0.8:1.8 to 1.8:0.8, and particularly preferably 0.9:1.5 to 1:1. If the molar ratio is outside the above range, the reaction tends not to proceed sufficiently.

[0057] The pH when reacting the metal-containing compound with the base is usually 4 to 9, preferably 5 to 8. If the pH is lower than the above range, the reaction tends not to proceed sufficiently. If the pH is higher than the above range, the EVOH resin composition of the present invention tends not to be obtained. The pH is adjusted by adjusting the amounts of the solution in which the metal-containing compound is dissolved or the slurry in which the metal-containing compound is dispersed, and the solution in which the base is dissolved.

[0058] The reaction temperature in the above reaction is usually 15 to 60° C., and preferably 20 to 40° C. If the reaction temperature is too low, the reaction tends not to proceed sufficiently, whereas if the reaction temperature is too high, the metal-containing compound tends to be decomposed by heat, and the EVOH resin composition of the present invention tends not to be obtained. The reaction time is usually 0.5 to 100 hours, preferably 1 to 70 hours, and the reaction pressure may be normal pressure.

[0059] [Method (II)] The above method (II) is a method in which a metal-containing compound is heated in a solution in which EVOH is dissolved to cause a reaction.

[0060] The above method (II) is usually carried out by further dissolving a metal-containing compound in a solution in which EVOH has been dissolved, and heating the resulting solution with stirring.

[0061] As the solvent for dissolving the EVOH and the metal-containing compound, the solvents listed in the above method (I) can be used. Among them, water and alcohols are preferred, and a mixed solvent of water and 1-propanol is particularly preferred.

[0062] As for the heating conditions, the solution is usually heated to a temperature of 20 to 100° C., preferably 50 to 95° C., and particularly preferably 70 to 90° C. If the reaction temperature is too low, the reaction tends not to proceed sufficiently, whereas if the reaction temperature is too high, the metal-containing compound tends to be decomposed by heat, and the EVOH resin composition of the present invention tends not to be obtained. The reaction time is usually 0.1 to 100 hours, preferably 0.5 to 30 hours, and particularly preferably 1 to 10 hours, and the reaction may be carried out under normal pressure.

[0063] [Method (III)] The above method (III) is a method in which a metal compound obtained by reacting a metal-containing compound with a base in advance is mixed with EVOH.

[0064] Examples of the base used in the above method (III) include hydroxides of alkali metals or alkaline earth metals. Among them, hydroxides of alkali metals are preferred, and sodium hydroxide is particularly preferred, because they have excellent reactivity with metal-containing compounds.

[0065] In the reaction between the metal-containing compound and the base, the metal-containing compound and the base may usually be mixed in a solution and reacted. The method of mixing the metal-containing compound and the base is not particularly limited, and examples thereof include a method of mixing a solution in which a metal-containing compound is dissolved with a solution in which a base is dissolved, and a method of mixing a slurry liquid in which a metal-containing compound is dispersed with a solution in which a base is dissolved. Among these, from the viewpoint of reaction efficiency, a method of mixing a solution in which a metal-containing compound is dissolved with a solution in which a base is dissolved is preferred. Furthermore, when an organic acid metal salt is used as the metal-containing compound, a method of adding a solution in which an organic acid metal salt is dissolved to a solution in which a base is dissolved and mixing them is preferred, and when an inorganic metal salt is used, a method of adding a solution in which a base is dissolved to a solution in which an inorganic metal salt is dissolved and mixing them is preferred.

[0066] As the solvent for dissolving the metal-containing compound and the base, the solvents listed in the above method (I) can be used, among which water is preferred from the viewpoint of ease of post-treatment.

[0067] The concentration of the metal-containing compound in the solution in which the metal-containing compound is dissolved is usually 0.01 to 3 mol / L, and preferably 0.05 to 2 mol / L. The concentration of the base in the solution obtained by dissolving the base in the solvent is usually 0.01 to 100 mol / L, preferably 0.05 to 30 mol / L, and particularly preferably 0.1 to 10 mol / L. If the concentrations of the metal-containing compound and the base are lower than the above ranges, the reaction tends not to proceed sufficiently, whereas if the concentrations of the metal-containing compound and the base are higher than the above ranges, side reactions tend to occur.

[0068] The molar ratio of the metal-containing compound to the base (metal-containing compound:base) is usually 0.5:2 to 2:0.5, preferably 0.8:1.8 to 1.8:0.8, and particularly preferably 0.9:1.5 to 1:1. If the molar ratio is outside the above range, the reaction tends not to proceed sufficiently.

[0069] The pH when reacting the metal-containing compound with the base is usually 4 to 9, preferably 5 to 8. If the pH is lower than the above range, the reaction tends not to proceed sufficiently. If the pH is higher than the above range, the generated metal compound tends to decompose. The pH can be adjusted by using a solution in which the metal-containing compound is dissolved or a solution in which the base is dissolved.

[0070] The reaction temperature in the above reaction is usually 15 to 60° C., and preferably 20 to 40° C. If the reaction temperature is too low, the reaction tends not to proceed sufficiently, whereas if the reaction temperature is too high, the metal-containing compound tends to be decomposed by heat, and the target metal compound tends not to be obtained. The reaction time is usually 0.5 to 100 hours, preferably 1 to 70 hours, and the reaction pressure may be normal pressure.

[0071] After the above reaction, the metal compound is obtained as a precipitate. The obtained metal compound may be used as it is, but it is preferably purified by washing, grinding, or other operations before use.

[0072] The method of mixing the metal compound obtained above with EVOH is not particularly limited, and known methods can be adopted. Among them, adding the metal compound to a solution in which EVOH is dissolved and stirring under reflux is preferable from the viewpoint of miscibility. As the solvent for dissolving EVOH, the solvents listed in the method (I) above can be used. Among them, a mixed solvent of water and 1-propanol is preferable.

[0073] By the above methods, the EVOH resin composition of the present invention containing EVOH and a metal compound and having an X-ray diffraction peak at 2θ = 2 to 15° when measured by wide-angle X-ray diffraction using CuKα radiation can be prepared. Among them, the method (II) is preferable from the viewpoint of operability. In addition, the EVOH resin composition prepared by each of the above methods may be used in a solution state or may be made into pellets or the like by known methods before use.

[0074] [Other Components] In the EVOH resin composition of the present invention, within a range that does not inhibit the effects of the present invention, compounding agents generally used in EVOH resin compositions, such as heat stabilizers, antioxidants, antistatic agents, colorants, ultraviolet absorbers, lubricants, plasticizers, light stabilizers, surfactants, antibacterial agents, desiccants, antiblocking agents, flame retardants, crosslinking agents, curing agents, foaming agents, crystal nucleating agents, antifogging agents, biodegradable additives, silane coupling agents, oxygen absorbers, etc., may be contained. These can be used alone or in combination of two or more.

[0075] <Film Containing EVOH Resin Composition> The film containing the EVOH resin composition of the present invention is obtained by forming a film of the composition containing the above EVOH resin composition, and preferably, it is obtained by forming a film of the above EVOH resin composition.

[0076] Examples of the method for forming the film include a method using a solution (coating liquid) of a composition containing an EVOH resin composition, a method of melt molding a pellet-shaped composition containing the EVOH resin composition of the present invention using an extruder, etc. Among these, the method using a solution (coating liquid) of a composition containing an EVOH resin composition is preferred.

[0077] As the coating liquid, the solution of the EVOH resin composition prepared by the above-mentioned method may usually be used as it is, or, if necessary, the solid content concentration may be adjusted before use. The solid content of the coating liquid is usually 0.5 to 30% by weight, and preferably 5 to 20% by weight. The solid content can be adjusted by using the solvents listed in the preparation method of the EVOH resin composition.

[0078] The film can be formed by any known method, such as a melt extrusion method, a casting method, a coating method, etc. Among these, the coating method is preferred.

[0079] Examples of the coating method include known methods such as bar coating, roll coating, die coating, gravure coating, comma coating, and screen printing.

[0080] After coating, a film made of the EVOH resin composition can be obtained by drying, for example, by heat treatment at 60 to 105° C. for 0.5 to 10 minutes. Furthermore, the above film may be subjected to a stretching operation such as uniaxial stretching or biaxial stretching, if necessary.

[0081] The film may be a single layer structure or a multilayer structure. The multilayer structure preferably has at least one layer made of the film. The multilayer structure may be formed by laminating the film formed, or may be laminated with another base resin.

[0082] The thickness of the film is usually 1 to 200 μm, preferably 1 to 100 μm, and particularly preferably 1 to 50 μm. When the formed film has a multi-layer structure, the thickness of the film is the total thickness of all the films made of the EVOH resin composition.

[0083] Examples of the base resin include polyethylene-based resins such as linear low-density polyethylene, low-density polyethylene, very low-density polyethylene, medium-density polyethylene, high-density polyethylene, ethylene-propylene (block and random) copolymers, and ethylene-α-olefin (α-olefin having 4 to 20 carbon atoms) copolymers; polypropylene-based resins such as polypropylene and propylene-α-olefin (α-olefin having 4 to 20 carbon atoms) copolymers; (unmodified) polyolefin-based resins such as polybutene, polypentene, and polycyclic olefin-based resins (polymers having a cyclic olefin structure in at least one of the main chain and side chain); and polyolefins obtained by treating with an unsaturated carboxylic acid or Examples of the polyolefin resin include a broad polyolefin resin including modified olefin resins such as unsaturated carboxylic acid modified polyolefin resins graft-modified with esters, ionomers, ethylene-vinyl acetate copolymers, ethylene-acrylic acid copolymers, ethylene-acrylic acid ester copolymers, polyester resins, polyamide resins (including copolymerized polyamides), polyvinyl chloride, polyvinylidene chloride, acrylic resins, polystyrene, vinyl ester resins, polyester elastomers, polyurethane elastomers, polystyrene elastomers, halogenated polyolefins such as chlorinated polyethylene and chlorinated polypropylene, aromatic or aliphatic polyketones, etc. These may be used alone or in combination of two or more. In addition, these base resins may be subjected to surface treatment such as corona treatment.

[0084] The film made of the EVOH resin composition of the present invention has excellent gas barrier properties under high humidity, and when the film is left standing under high humidity, it is preferable that the film has even more excellent gas barrier properties, particularly oxygen barrier properties, under high humidity. The principle by which such an effect is obtained is not clear, but it is presumed that the EVOH molecules are plasticized by leaving the film standing under high humidity, and the metal compounds dispersed in the film interact with the EVOH or are localized on the surface of the film.

[0085] In the present invention, "high humidity" means 20±5° C. and 90±10% RH. The standing time is usually 70 hours or more, preferably 300 hours or more, and more preferably 500 hours or more. The upper limit of the standing time is usually 1,000 hours.

[0086] The oxygen permeability of a film made of an EVOH resin composition is 15cc·20μm / m 2 ·day·atm(cm 3 20μm / m 2 ·day·atm) or less, and 10cc·20μm / m 2 ·day·atm or less is preferable, and 5cc·20μm / m 2 It is particularly preferable that the oxygen permeability is less than 0 cc·day·atm. Note that the oxygen permeability is measured in an environment of 20°C and 90% RH, and the lower limit of the oxygen permeability is usually 0 cc·20 μm / m 2 ·day·atm. The oxygen permeability can be determined by an oxygen permeability measuring device.

[0087] The EVOH resin composition of the present invention and a film made of the EVOH resin composition are useful as packaging materials, and can be suitably used in particular as packaging materials for foods, medicines, and the like. EXAMPLES

[0088] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples as long as it does not depart from the gist of the present invention. In the following, "parts" refers to parts by weight.

[0089] Prior to the examples, the following EVOH was prepared.

[0090] [Hydrophilic resin] EVOH1 (ethylene structural unit content: 44 mol%, MFR: 3 g / 10 min, saponification degree: 99.6 mol%, moisture content: 0.3 wt%) EVOH2 (ethylene structural unit content: 29 mol%, MFR: 4 g / 10 min, saponification degree: 99.6 mol%, moisture content: 0.3 wt%) EVOH3 (ethylene structural unit content: 25 mol%, MFR: 4 g / 10 min, saponification degree: 99.6 mol%, moisture content: 0.3 wt%)

[0091] <Example 1> 5 parts of EVOH1 and 1.0 part of zinc acetate dihydrate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) in terms of metal to EVOH were added to 45 parts of a mixed solvent of water / 1-propanol = 4 / 6 (volume ratio), and the mixture was heated and stirred at 87 ° C (under reflux) for 2 hours to obtain an EVOH resin composition containing a metal compound (a reaction product of zinc acetate) obtained by reacting zinc acetate dihydrate. This solution was allowed to cool to 55 ° C to prepare a coating liquid. The obtained coating liquid was applied to the corona-treated surface of a PET substrate having a thickness of 12 μm that had been corona-treated using a wire bar #24, and dried at 80 ° C for 5 minutes. This process was repeated twice to obtain a two-layer film in which a film layer having a thickness of 6 μm was laminated on the PET substrate. The obtained film was left to stand for 600 hours under humidity-controlled conditions of 20 ° C and 90% RH to prepare a film.

[0092] <Example 2> A film was produced in the same manner as in Example 1 and prepared under the same humidity control conditions, except that the volume ratio of the mixed solvent used in Example 1 (water / 1-propanol) was changed to 1 / 1 and EVOH1 was changed to EVOH2.

[0093] <Example 3> [Synthesis of hydroxyalkyl carboxylate zinc reactants] 100 parts of 0.79 mol / L 6-hexanolactone-methanol solution was added dropwise to 200 parts of 0.39 mol / L sodium hydroxide-methanol solution, and the mixture was stirred at 67 ° C for 5 hours to react. After that, the mixture was allowed to cool to 24 ° C, and 100 parts of 0.79 mol / L zinc nitrate-methanol solution was added dropwise to the mixture, and the mixture was stirred at 24 ° C for 3 days to react. The reaction liquid after the reaction was separated into a precipitate and a filtrate by vacuum filtration, and the solvent contained in the filtrate was removed with an evaporator, and then 40 parts of water was added to the precipitated solid and cooled to 4 ° C. The white solid that did not dissolve was filtered out by vacuum filtration. Then, cold water was added to the white solid obtained as the residue, and the mixture was stirred and filtered again to wash the white solid. Finally, the filtered white solid was dried at normal pressure at 60 ° C for two days to obtain a zinc hydroxyalkyl carboxylate. 0.5 g of the obtained zinc hydroxyalkylcarboxylate was dissolved in 20 parts of water and stirred at 24°C, while 20 parts of 0.12 mol / L aqueous sodium hydroxide solution was slowly added dropwise thereto, and the mixture was reacted by stirring at 25°C for 48 hours. After the reaction, the deposited white precipitate was filtered off by vacuum filtration. The white solid obtained as the residue was piston-washed three times with water, and dried at 60°C under normal pressure to obtain a metal compound (a reaction product of zinc hydroxyalkylcarboxylate).

[0094] [Creating the film] 5 parts of EVOH3 were added to 45 parts of a mixed solvent of water / 1-propanol = 1 / 1 (volume ratio), and the mixture was heated and stirred at 87 ° C for 1 hour to completely dissolve the EVOH. The solution was allowed to cool to 55 ° C, and 0.5 parts of the metal compound (a reaction product of zinc hydroxyalkyl carboxylate) obtained above was added to 100 parts of EVOH in terms of metal to obtain an EVOH resin composition. The solution was stirred at 87 ° C (under reflux) for 2 hours, and then allowed to cool to 55 ° C to prepare a coating liquid. The obtained coating liquid was applied to the corona-treated surface of a 12 μm-thick PET substrate that had been corona-treated using a wire bar #24, and dried at 80 ° C for 5 minutes. This process was repeated twice to obtain a two-layer film in which a film layer of 6 μm thickness was laminated on the PET substrate. The obtained film was left to stand for 533 hours under humidity-controlled conditions of 20 ° C and 90% RH to prepare a film.

[0095] <Comparative Example 1> 5 parts of EVOH3 were added to 45 parts of a mixed solvent of water / 1-propanol = 1 / 1 (volume ratio), and the mixture was heated and stirred at 87 ° C for 1 hour to completely dissolve the EVOH. The solution was allowed to cool to 55 ° C, and 0.1 parts of zinc oxide (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) was added in terms of metal to 100 parts of EVOH, and the mixture was stirred for 2 hours at 55 ° C to prepare an EVOH resin composition (coating liquid). A film was produced from the obtained coating liquid in the same manner as in Example 1, and prepared under the same humidity control conditions.

[0096] <Comparative Example 2> A film was prepared in the same manner and under the same humidity conditioning conditions as in Example 1, except that zinc acetate dihydrate was not added.

[0097] <Comparative Example 3> A film was produced in the same manner as in Example 2, except that zinc acetate dihydrate was not added, and the film was prepared under the same humidity control conditions.

[0098] The wide-angle X-ray diffraction and gas barrier properties were measured under the following conditions using the films obtained above in Examples 1 to 3 and Comparative Examples 1 to 3. The results are shown in Table 1 below.

[0099] [Wide-angle X-ray diffraction (XRD) measurement of film] The EVOH resin composition film obtained above was peeled off from the PET film and laminated to a thickness of 30 μm or more to prepare a sample. Wide-angle X-ray diffraction measurement of this sample was carried out under the following conditions. [Measurement conditions] Equipment used: D8 DISCOVER (manufactured by Bruker Japan) Detector: 2D detector VANTEC-500 (manufactured by Bruker Japan) Voltage: 50kV Current: 100mA Camera length: 100mm Measurement method: Reflection method Accumulation time: 30 minutes for Examples 1 and 2 and Comparative Examples 1 to 3, and 60 minutes for Example 3 Wavelength: CuKα radiation (Kα1 and Kα2 are not separated) Detector position: 2θ=10° X-ray incident angle: θ=0.3° Conditions for one-dimensionalization in the 2θ direction: 2θ=0 to 35°, azimuth angle (chi)=-95 to -85° One-dimensional azimuth angle direction: In Examples 1 and 2, 2θ = 6.0 to 7.0°, azimuth angle (chi) = -180 to 0° After the X-ray diffraction measurement, the obtained diffraction image was converted into one dimension in the azimuth angle range of -180 to 0° in the range of 2θ = 6.0 to 7.0°, and the azimuth angle dependence of the diffraction intensity was confirmed. At this time, if a diffraction peak was observed at an azimuth angle of -90°, it was determined that the EVOH resin composition has a diffraction peak at 2θ = 6.0 to 7.0°. In Example 3, X-ray diffraction measurements were performed at 2θ=3.5 to 4.5° and azimuth angle (chi)=-180 to 0°, and the obtained diffraction image was converted into one-dimensional data in the azimuth angle range of -180 to 0° in the range of 2θ=3.5 to 4.5° to confirm the azimuth angle dependence of the diffraction intensity. If a diffraction peak was observed at an azimuth angle of -90°, it was determined that the EVOH resin composition had a diffraction peak at 2θ=3.5 to 4.5°.

[0100] [Gas barrier properties] The oxygen permeability of the obtained EVOH resin composition film was measured under conditions of 20° C. and 90% RH using an oxygen permeability measuring device (OX-TRAN100A, manufactured by MOCON).

[0101] [Table 1]

[0102] As can be seen from Table 1 above, the EVOH resin compositions of Examples 1 to 3, which contain EVOH and a metal compound and have a peak on the low angle side (2θ=2 to 15°) in wide-angle X-ray diffraction measurement, had excellent oxygen barrier properties under high humidity conditions. On the other hand, the EVOH resin composition of Comparative Example 1, which had no peak at low angles in wide-angle X-ray diffraction measurement, and the EVOHs of Comparative Examples 2 and 3 all had poor oxygen barrier properties.

[0103] In the above embodiment, specific embodiments of the present invention are shown, but the above embodiment is merely illustrative and should not be interpreted as being limiting. Various modifications that are obvious to those skilled in the art are intended to be within the scope of the present invention. [Industrial Applicability]

[0104] The EVOH resin composition of the present invention is useful as a packaging material, particularly as it has excellent gas barrier properties, particularly oxygen barrier properties, under high humidity conditions, and can be suitably used as a packaging material for foods, medicines, etc.

Claims

1. An ethylene-vinyl alcohol-based copolymer resin composition containing an ethylene-vinyl alcohol-based copolymer and a metal compound, the metal compound is at least one of a reaction product of zinc acetate and a reaction product of zinc hydroxyalkylcarboxylate having an alkyl group with 2 to 8 carbon atoms; The ethylene-vinyl alcohol-based copolymer resin composition is characterized in that, when the ethylene-vinyl alcohol-based copolymer resin composition is measured by wide-angle X-ray diffraction using CuKα radiation, it has an X-ray diffraction peak at 2θ = 2 to 15°.

2. 2. The ethylene-vinyl alcohol copolymer resin composition according to claim 1, wherein the content of the metal compound in terms of metal is 0.01 to 10 parts by weight based on 100 parts by weight of the ethylene-vinyl alcohol copolymer.

3. 3. A film comprising the ethylene-vinyl alcohol copolymer resin composition according to claim 1.

4. The oxygen permeability of the above film under conditions of 20°C and 90% RH is 15cc・20μm / m 2 4. The film according to claim 3, characterized in that it has a viscosity of not more than 1.times.day.atm.

5. A multilayer structure having at least one layer made of the film according to claim 3 or 4.

Citation Information

Patent Citations

  • Coating material and coated film using the same

    JP2004091521A

  • Method for producing composition

    JP2004323787A

  • Method of producing composite material

    JP2012087215A

  • Ethylene - vinyl ester-based copolymer saponification product composition and production method therefor

    WO2016088862A1

  • Resin composition and multilayered structure using same

    WO2018088347A1